PENINGKATAN KETERAMPILAN GURU NONKEPENDIDIKAN DALAM MEMBUKA PELAJARAN MELALUI SUPERVISI KLINIS PADA SMK BINAAN KABUPATEN BOJONEGORO - Imam Sujianto (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2022)
This study aims to improve the skills of non-educational teachers in opening lessons through clinical supervision at Foster Vocational Schools in Bojonegoro Regency. This research was conducted at Foster Vocational Schools in Bojonegoro Regency. The school is a school fostered by researchers who serve as supervisors. The subjects in this study were productive teachers at SMK Taruna Mandiri Ngasem, Wali Songo Sugihwaras Vocational School, and Al Kyai Sukosewu Vocational School. This research was carried out for two months, from September to October 2021. From the results of the research it can be concluded that the effectiveness of clinical supervision was able to improve the skills of non-educational teachers at Foster Vocational Schools in Bojonegoro Regency in opening lessons to expedite the learning process. The results achieved in cycle I averaged 77.50, and in cycle II achieved an average score of 91.67 according to the researcher's target, namely the average score of 86 and above. By increasing the skills of non-educational teachers in opening lessons, the learning process becomes more effective and efficient.